SlARF4, an Auxin Response Factor Involved in the Control of Sugar Metabolism during Tomato Fruit Development - Sagar, Maha; Chervin, Christian; Mila, Isabelle; Hao, Yanwei; Roustan, Jean-Paul; Benichou, Mohamed; Gibon, Yves; Biais, Benoît; Maury, Pierre; Latché, Alain; Pech, Jean-Claude; Bouzayen, Mondher; et al. (Plant physiology (Bethesda), 2013)
Successful completion of fruit developmental programs depends on the interplay between multiple phytohormones. However, besides ethylene, the impact of other hormones on fruit quality traits remains elusive. A previous study has shown that down-regulation of SlARF4, a member of the tomato (Solanum lycopersicum) auxin response factor (ARF) gene family, results in a dark-green fruit phenotype with increased chloroplasts (Jones et al., 2002). This study further examines the role of this auxin transcriptional regulator during tomato fruit development at the level of transcripts, enzyme activities, and metabolites. It is noteworthy that the dark-green phenotype of antisense SlARF4-suppressed lines is restricted to fruit, suggesting that SlARF4 controls chlorophyll accumulation specifically in this organ. The SlARF4 underexpressing lines accumulate more starch at early stages of fruit development and display enhanced chlorophyll content and photochemical efficiency, which is consistent with the idea that fruit photosynthetic activity accounts for the elevated starch levels. SlARF4 expression is high in pericarp tissues of immature fruit and then undergoes a dramatic decline at the onset of ripening concomitant with the increase in sugar content. The higher starch content in developing fruits of SlARF4 down-regulated lines correlates with the up-regulation of genes and enzyme activities involved in starch biosynthesis, suggesting their negative regulation by SlARF4. Altogether, the data uncover the involvement of ARFs in the control of sugar content, an essential feature of fruit quality, and provide insight into the link between auxin signaling, chloroplastic activity, and sugar metabolism in developing fruit.